High Net Primary Production of Mediterranean Seagrass (Posidonia oceanica) Meadows Determined With Aquatic Eddy Covariance - Koopmans, Dirk; Holtappels, Moritz; Chennu, Arjun; Weber, Miriam; de Beer, Dirk (Frontiers in Marine Science, 2020)
We report primary production and respiration of Posidonia oceanica meadows determined with the non-invasive aquatic eddy covariance technique. Oxygen fluxes were measured in late spring at an open-water meadow (300 m from shore), at a nearshore meadow (60 m from shore), and at an adjacent sand bed. Despite the oligotrophic environment, the meadows were highly productive and highly autotrophic. Net ecosystem production (54 to 119 mmol m-2 d-1) was about one-half of gross primary production. In adjacent sands, net primary production was a tenth- to a twentieth smaller (4.6 mmol m-2 d-1). Thus, P. oceanica meadows are an oasis of productivity in unproductive surroundings. During the night, dissolved oxygen was depleted in the open-water meadow. This caused a hysteresis where oxygen production in the late afternoon was greater than in the morning at the same irradiance. Therefore, for accurate measurements of diel primary production and respiration in this system, oxygen must be measured within the canopy. Generally, these measurements demonstrate that P. oceanica meadows fix substantially more carbon than they respire. This supports the high rate of organic carbon accumulation and export for which the ecosystem is known.